2021
DOI: 10.1007/s00392-021-01914-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world applicability and impact of early rhythm control for European patients with atrial fibrillation: a report from the ESC-EHRA EORP-AF Long-Term General Registry

Abstract: Background Use of rate/rhythm control is essential to control symptoms in patients with atrial fibrillation (AF). Recently, the EAST-AFNET 4 trial described how early rhythm control strategy was associated with a lower risk of adverse clinical outcomes. Objectives The aim was to evaluate the real-world applicability and impact of an early rhythm control strategy in patients with AF. Methods Use of an early rhythm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This may contribute to explain why in a proportion of patients in part similar to EAST AF patients, the choice of strategy in our daily practice was in favor of rhythm control only in less than 20% of cases (data not shown). While the current results of the EAST AF may provide a guide for decision making in appropriately selected patients, a recent analysis from the EORP-AF registry showed that the use of an early rhythm control strategy was not independently associated with a lower rate of major adverse events and associated with a higher use of health care resources [44].…”
Section: Discussionmentioning
confidence: 83%
“…This may contribute to explain why in a proportion of patients in part similar to EAST AF patients, the choice of strategy in our daily practice was in favor of rhythm control only in less than 20% of cases (data not shown). While the current results of the EAST AF may provide a guide for decision making in appropriately selected patients, a recent analysis from the EORP-AF registry showed that the use of an early rhythm control strategy was not independently associated with a lower rate of major adverse events and associated with a higher use of health care resources [44].…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, no difference in the primary outcome between early rhythm control and "no rhythm control patients" adherent to the ABC pathway was evident. 28 Therefore, whether the better outcomes of patients assigned to rhythm control in the EAST-AFNET 4 trial were solely due to "early" intervention or because of more regular and structured follow-up was unclear. Our study was performed based on data acquired from the routine daily care with less structured management protocols, and our findings may provide complimentary "real-world" data to support the generalizability of the results of the EAST-AFNET 4 trial into daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with current recommendation of not considering AF ablation as a last-resort therapeutic strategy, but rather to propose it before the development of atrial dilatation and atrial cardiomyopathy [ 45 , 46 , 47 , 48 ], which imply a reduced effectiveness of the intervention. Recent data on AF ablation [ 12 , 49 , 50 ] and more general data from EAST AF trial indicate that the success of rhythm control strategies is markedly influenced by the time from AF clinical detection [ 51 , 52 , 53 ]. It will be matter of additional investigation to assess the influence of asymptomatic AF episodes, which could be present in a substantial number of patients, with no differences in the impact on hard clinical outcomes, such as stroke [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%